Komunikasi Pemasaran Cinderamata Khas Banten Produk Warga Kampung Pekijing - Nana Sutisna Amdan; Yayan S aryani; Muhaemin Muhaemin; Aditya Ramadhan; Rd. Nia Kania Kurniawati; Naniek Afrilla (Jurnal Pengabdian Pada Masyarakat, 2022)
MARKETING COMMUNICATION OF SPECIAL BANTEN SOUVENIR PRODUCTS PEKIJING VILLAGE. Pekijing, is a village located in Kalanganyar Village, Serang City, has shown its existence by becoming a Tourism Village established by the Serang City Government in 2021. Pekijing Village continues to improve by carrying out various community empowerment efforts. One of them is structuring and increasing the capacity of human resources in the management of natural resources. There are many MSME products produced by Pekijing residents, such as various woven bamboo, carvings, miniature Banten towers, key chains, local specialties, to products made from plastic waste, such as flowers, or mats and mask connectors. However, obstacles are still being faced, namely the problem of capital and product marketing to be accepted by the market. To optimize the Marketing of Banten Special Souvenirs for the Pekijing Village residents, the Master of Communication Studies Program at Sultan Ageng Tirtayasa University Conducts Community Service activities in Pekijing Village, to help encourage active community participation in production activities, creativity development and marketing of the products owned. The community is encouraged not only to be creative in building tourist destinations and production, but also to have a role as marketing by optimizing public spaces in the digital realm, especially in the use of online stores, social media, such as Facebook, YouTube, Instagram and Tiktok.